2009
DOI: 10.1002/jsfa.3598
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth characteristics and bioactive potential of Lactobacillus acidophilus in a soy‐based cream cheese

Abstract: BACKGROUND: Soy-based products have received much attention lately as dairy replacers and carriers for probiotics, without the cholesterol and lactose intolerance factors. We have previously developed a soy cream cheese product and would like to evaluate its suitability as a carrier for probiotic microorganisms. Soy cream cheese is commercially uncommon, while a probiotic soy cream cheese is yet to be available in the market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
1
13
0
3
Order By: Relevance
“…However, they are poor in meltability and lack of hardness (Shurtleff and Aoyagi 2013). Nowadays food researches develop or produce soft cheeses using soy milk, considering the fact of high water retention capacity of soy proteins (Li et al 2013;Liong et al 2009;Rinaldoni et al 2014). However, seems no much awareness to use soy milk in mozzarella cheese production.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are poor in meltability and lack of hardness (Shurtleff and Aoyagi 2013). Nowadays food researches develop or produce soft cheeses using soy milk, considering the fact of high water retention capacity of soy proteins (Li et al 2013;Liong et al 2009;Rinaldoni et al 2014). However, seems no much awareness to use soy milk in mozzarella cheese production.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have demonstrated that probiotics possess varying levels of α‐galactosidase. Fung et al 8 demonstrated that probiotics could hydrolyse α‐galactosyl oligosaccharides in soy whey, while Liong et al 9 reported that incorporation of probiotics with α‐galactosidase activity could increase the hydrolysis of soybean oligosaccharides and consequently reduce their antinutritive properties in soy cream cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of soy products with probiotics. Serek sojowy Soy cream cheese L. acidophilus > 10 7 [20] Tofufa / Tofufa L. bulgaricus, L. fermentum > 10 6 [24] Przeprowadzono badania dotyczące wpływu fermentacji produktów sojowych na zawartość wybranych substancji bioaktywnych. Yeo i Liong [38] określili wpływ prebiotyków (fruktooligosacharydów, inuliny, mannitolu, maltodekstryny i pektyny) na bioaktywność fermentowanego mleka sojowego i stwierdzili, że taka suplementacja sprzyjała zmniejszaniu ciśnienia w badaniach in vitro i produkcję bioaktywnych aglikonów.…”
Section: T a B E L Aunclassified
“…Liong i wsp. [20] wytworzyli serek sojowy ze zmiksowanego tofu z olejem palmowym (10 %), karagenem (4 %), pektyną (1 %), maltodekstryną (4,05 %) i solą (0,96 %). Do produktu dodano kulturę L. acidophilus FTCC 0291 w liczbie ok. 10 8 jtk/g.…”
Section: T a B E L Aunclassified